Pedagogical Biography from the Standpoint of Scientific Research - Kateryna Binytska; Galyna Buchkivska; Yaroslav Nahornyi (Pedagogical Discourse, 2022)
Our research analyzed some aspects of the outlined topic, in particular the question of determining the place of biographical data in the system of scientific-pedagogical discourse. It has been found that at the beginning of the XXIst century, a tendency towards biographical revitalization is noted in the pedagogical science of Ukraine, scientists actively interpret the historical-pedagogical experience, evaluate and compare the past with the present through the life path and scientific-pedagogical activity of well-known or little-known pedagogues, educators who, thanks to their scientific-pedagogical successes have become symbols of separate historical periods, which personify the turning points in the progress of the Ukrainian people and the development of education, science, economy, culture, etc.The article emphasizes that the analysis of the experience of the leading countries of the world is important for the study of pedagogical biography. Therefore, we analyzed the development of the International Association of Pedagogical Biography in the USA.It is summarized that biographical studies today occupy an important place in the history of pedagogy and make it possible to personify the history of the development of the field of education, to evaluate the contribution of researchers, teachers, educationalists involved in the conduct of scientific-pedagogical researches and the organization of educational practice. It is emphasized that in the context of the use of biography in scientific-pedagogical research, the method of organizing bibliographic information and research tools are of great importance. For pedagogical biography, this is a conceptual apparatus chosen by the researchers themselves.